Pregunta
upstudy study bank question image url

Solve the system by elimination. Enter your answer as an ordered pair or type none or infinite. \( \left\{\begin{array}{c}8 x-3 y=-11 \\ 2 x-5 y=27\end{array}\right. \)

Ask by Chadwick Adkins. in the United States
Dec 03,2024

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solution is \( (x, y) = (-4, -7) \).

Solución

Solve the system of equations \( 8x-3y=-11;2x-5y=27 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}8x-3y=-11\\2x-5y=27\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{-11+3y}{8}\\2x-5y=27\end{array}\right.\) - step2: Substitute the value of \(x:\) \(2\times \frac{-11+3y}{8}-5y=27\) - step3: Reduce the fraction: \(\frac{-11+3y}{4}-5y=27\) - step4: Multiply both sides of the equation by LCD: \(\left(\frac{-11+3y}{4}-5y\right)\times 4=27\times 4\) - step5: Simplify the equation: \(-11-17y=108\) - step6: Move the constant to the right side: \(-17y=108+11\) - step7: Add the numbers: \(-17y=119\) - step8: Change the signs: \(17y=-119\) - step9: Divide both sides: \(\frac{17y}{17}=\frac{-119}{17}\) - step10: Divide the numbers: \(y=-7\) - step11: Substitute the value of \(y:\) \(x=\frac{-11+3\left(-7\right)}{8}\) - step12: Simplify: \(x=-4\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-4\\y=-7\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-4\\y=-7\end{array}\right.\) - step15: Rewrite: \(\left(x,y\right) = \left(-4,-7\right)\) The solution to the system of equations by the elimination method is \( (x, y) = (-4, -7) \).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To solve the system by elimination, we can first manipulate the equations to eliminate one variable. Let's multiply the second equation by 4 so that the coefficients of \(x\) in both equations will match: 1. First equation: \(8x - 3y = -11\) 2. Second equation (multiplied by 4): \(8x - 20y = 108\) Now, we subtract the first equation from the second: \((8x - 20y) - (8x - 3y) = 108 - (-11)\) This simplifies to: \(-20y + 3y = 108 + 11\) \(-17y = 119\) Now, divide both sides by \(-17\): \(y = -\frac{119}{17}\) Next, substitute \(y\) back into one of the original equations to find \(x\). We can use the first equation: \(8x - 3\left(-\frac{119}{17}\right) = -11\) This becomes: \(8x + \frac{357}{17} = -11\) To remove the fraction, multiply the entire equation by 17: \(136x + 357 = -187\) Now, solve for \(x\): \(136x = -187 - 357\) \(x = -\frac{544}{136} = -4\) Finally, we have the solution as the ordered pair: \((-4, -\frac{119}{17})\)

preguntas relacionadas

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad